Physical health trajectories of young people commenced on clozapine. (20th March 2021) - O'Donoghue, B.; Mujanovic, A.; Young, S.; Bridson, T.; Mora, L.; Bismark, M.; Cocks, J.; Siskind, D.; McGorry, P.
Abstract: Objectives: Clozapine is the most effective antipsychotic medication, but it has the highest propensity for metabolic side effects. A clozapine clinic was established within an early intervention for psychosis service to facilitate the timely commencement of clozapine and to manage the associated adverse effects. This study describes the changes in the weight, body mass index (BMI), waist circumference and blood pressure after 6 months in young people commenced on clozapine. Method: This was a prospective cohort study of all young people, aged 15–24 years, commenced on clozapine within an early intervention service in Melbourne, Australia, between 01.04.2016 and 30.06.2018. Continuous data were analyzed with paired t -test and categorical with Wilcoxon signed-rank test. Results: Twenty-six young people received 6 months of treatment with clozapine, of whom the mean age was 19.8 years (s.d. ±3.1) and 66.7% were male. After 6 months, the mean weight gain was 5.1 kg (s.d. ±10.1 kg) and over half (53.8%) gained clinically significant weight. The proportion of young people classified as either overweight or obese rose from 69.2% to 88.5% ( p = 0.006). The proportion of young people with a waist circumference above the recommended parameters increased from 57.9% to 78.9% ( p = 0.008). Hypertension was present in 30%, and after 6 months, 45% had hypertension ( p = 0.64). Metformin was prescribed to 34.6%, typically to those with the greatest and most rapid weight gain. Conclusion: Among young people with treatment resistant psychosis, clozapine is associated with significant metabolic side effects in the early stages of commencement. More interventions aimed at attenuating this weight gain are needed.